The Relationship Between Positive Reinforcement and Learning Outcomes Feedback in Increasing The Learning Motivation of Fifth-Grade Students - Rohmah Faristin; Yuniawatika; Sri Murdiyah (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2022)
This study aims to determine the relationship between positive reinforcement and learning outcomes feedback in increasing the learning motivation of fifth-grade students. This type of research uses ex post facto research with the determination of research respondents taken from fifth-grade students in Bolorejo Tulungagung. This data collection uses questionnaires, observations, interviews, and documentation. Analysis of research data using simple correlation and multiple correlations with a significance level of 0.05. Positive reinforcement has a relationship with learning motivation with a contribution of 24.7 percent. There is a relationship between learning outcomes feedback and learning motivation with a contribution of 92.8 percent. Positive reinforcement and feedback simultaneously have a relationship with learning motivation with the acquisition of a contribution of 93.2 percent. Based on the results of the study, it was concluded that there was a positive reinforcement relationship and feedback with the learning motivation of fifth-grade elementary school students in Bolorejo Tulungagung. Penelitian ini bertujuan untuk mengetahui hubungan antara positive reinforcement dan feedback hasil belajar terhadap peningkatan motivasi belajar siswa kelas V. Jenis penelitian ini menggunakan penelitian ex post facto dengan penentuan responden penelitian diambil dari siswa kelas V SDN 1 Bolorejo, SDN 2 Bolorejo dan SDN 3 Bolorejo. Pengumpulan data ini menggunakan angket, observasi, wawancara dan dokumentasi. Analisis data penelitian menggunakan korelasi sederhana dan korelasi ganda dengan taraf signifikansi 0,05. Positive reinforcement memiliki hubungan terhadap motivasi belajar dengan perolehan sumbangsih sebesar 24,7 persen. Ada hubungan feedback hasil belajar terhadap motivasi belajar siswa kelas V Sekolah Dasar di Bolorejo Tulungagung. Feedback hasil belajar memiliki hubungan terhadap motivasi belajar dengan perolehan sumbangsih sebesar 92,8 persen. Positive reinforcement dan feedback secara simultan memiliki hubungan terhadap motivasi belajar dengan perolehan sumbangsih sebesar 93,2 persen. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa ada hubungan positive reinforcement dan feedback terhadap motivasi belajar siswa kelas V Sekolah Dasar di Bolorejo Tulungagung.